2003
DOI: 10.1034/j.1600-0854.2003.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of Synaptotagmin 1 Is Mediated by a Novel, Tryptophan‐Containing Motif

Abstract: The rate at which a membrane protein is internalized from the plasma membrane can be regulated by revealing a latent internalization signal in response to an appropriate stimulus. Internalization of the synaptic vesicle membrane protein, synaptotagmin 1, is controlled by two distinct regions of its intracytoplasmic C2B domain, an internalization signal present in the 29 carboxyterminal (CT) amino acids and a separate regulatory region. We have now characterized the internalization motif by mutagenesis and foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 71 publications
(92 reference statements)
0
28
0
Order By: Relevance
“…In this motif, it has been suggested that the hydroxyl group of tyrosine is essential for recognition by AP-2 m2 (Owen and Evans, 1998). However, the neonatal Fc receptor and synaptotagmin 1 have been found to internalize through direct binding of their tryptophan-containing motif, WxxW, to AP-2 m2 (Jarousse et al, 2003;Wernick et al, 2005;Wu and Simister, 2001). These studies suggest that aromatic amino acids in this sequence are sufficient for AP-2 m2 recognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this motif, it has been suggested that the hydroxyl group of tyrosine is essential for recognition by AP-2 m2 (Owen and Evans, 1998). However, the neonatal Fc receptor and synaptotagmin 1 have been found to internalize through direct binding of their tryptophan-containing motif, WxxW, to AP-2 m2 (Jarousse et al, 2003;Wernick et al, 2005;Wu and Simister, 2001). These studies suggest that aromatic amino acids in this sequence are sufficient for AP-2 m2 recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan is an aromatic amino acid, as is tyrosine, and isoleucine is a canonical hydrophobic amino acid. Importantly, the neonatal Fc receptor and the synaptic vesicle membrane protein, synaptotagmin 1, have been reported to use a WxxW motif instead of the YxxW sequence for AP-2 m2 binding and internalization (Jarousse et al, 2003;Wernick et al, 2005;Wu and Simister, 2001). Therefore, the ability of the M1-mAChR Cterminal WxxW motif to bind to the AP-2 m2 subunit was examined in a GST pulldown assay.…”
mentioning
confidence: 99%
“…In addition, a body of evidence implicates synaptotagmin as a regulator of endocytosis (14)(15)(16)(17). Caenorhabditis elegans lacking a functional SytI gene show a depletion of synaptic vesicles at nerve terminals, consistent with a defect in endocytosis (14).…”
mentioning
confidence: 99%
“…Liposome studies suggest a direct fusogenic role for SytI, in which shallow insertion of the C 2 region into target membranes induces curvature to destabilize the lipid bilayer and form the fusion pore opening (1,3). Studies in mice, Drosophila, and C. elegans show that SytI also regulates the kinetics of endocytosis at nerve terminals, apparently in a clathrin-mediated manner (1,4).…”
mentioning
confidence: 99%